Factors influencing consumer attitudes towards e-commerce: a study on online shopping of apparel in the UK - Bayona Baquero, Paula Ximena (2020)
With the increased use of technology, e-commerce has created valuable opportunities for UK ‘bricks-and-clicks’ retailers. This business model is well-known for having a strong online and offline presence in the apparel sector (Debenhams, John Lewis and Partners, House of Fraser, and Marks & Spencer Group). This has inevitably impacted traditional consumer behaviors as people are now able to be active actors in their purchasing experience. Through the use of digital channels, consumers are able to have access to more information than ever before – which directly influences their attitudes towards purchasing apparel via the Internet.